Phenomenology Study of Culture and Academic Shock in the New Student’s Perspektive DIII Nursing Study Program - Evy Aristawati; Bagus Dwi Cahyono; Nurul Huda (Jurnal Keperawatan, 2022)
Culture and Academic Shock is one of the unavoidable challenges for students who have just been accepted into a college. The type of research used is a combination research (mixed methods) between qualitative and quantitative research. From the results of interviews with 6 participants, researchers obtained data that a new student of theirs was a student who came from an environment that was culturally different from the area where they were overseas. They come with the aim of going to college, staying for a certain period of time or not for a long period of time, usually with the intention of returning home and with one thing that becomes the main motivation, namely to complete their studies at the university located in their new environment. Conclusion From the results of interviews that researchers have conducted on six overseas student informants from outside Pasuruan consisting of early semester students, it shows that a period of culture shock will be experienced by every overseas student who has just entered the initial semester of lectures, only culture shock that occurs every year. Individuals differ about the extent to which culture shock will affect their lives.